Pemberdayaan Kelompok Tani Mubarakah di Kabupaten Agam Melalui Pengembangan Usaha Pupuk Kompos - Reswati Reswati; Tinda Afriyani; Dian Hafizah; Fayyadh Atsil Muhadzid; Annisa Kamila; Rifqi Aulia (Jurnal Hilirisasi IPTEKS, 2025)
The Mubarakah Farmers Group, established in 2009, is located in Nagari Sungai Landia, Agam Regency, and manages several business units, including cattle raising, crop production, and compost production. Although the group produces high-quality organic compost, sales remained low due to limited product recognition, weak product branding, and the absence of effective marketing strategies. Strengthening promotional efforts, particularly through digital approaches, was therefore essential to expanding market reach and improving members’ income. This Community Service program applied a capacity-building approach focusing on branding and digital marketing innovations for local farmer groups. Activities included brand and label development, packaging improvement, product arrangement and storage training, creation of promotional media, and utilization of social media platforms. Program effectiveness was measured through indicators such as sales volume, customer reach, and online engagement. This intervention generated measurable improvements. Monthly sales increased two to three times, from an average of 0-500 kg to 1,000-1,500 kg. Correspondingly, monthly revenue increased from IDR 0-400,000 to IDR 800,000-1,200,000. Strengthened social media promotion expanded product visibility, leading to increased customer inquiries and broader distribution coverage. The integration of branding and digital marketing proved effective in enhancing the competitiveness of locally produced organic compost, demonstrating a novel approach within community-based agricultural enterprises. This program offers both academic and practical contributions by demonstrating that structured branding and digital promotional strategies can significantly enhance the business performance and economic resilience of local farmer groups.